The portormin (dunbeath) runestone - Findell, Martin (University of Oslo, Museum of Cultural Heritage, 2016)
A stone with a short runic inscription was discovered on the beach at Portormin Harbour in Dunbeath, Caithness, in 1996. The find attracted some press attention at the time, but has been largely ignored by the runological community amid doubts over its authenticity. There has, however, been no detailed discussion of the stone in a public arena. A description of the inscription is followed by discussion of several interpretations. There are good reasons for suspecting that the carvings are of modern origin, but the matter cannot be settled with certainty; the case invites comparison with the controversies surrounding runic inscriptions in North America.